Journey Mapping of Chinese Women Undergoing Termination Due to Fetal Abnormalities: A Thematic Content Analysis Based on Social Media Diaries - Da C; Shi J; Ma P; Wu C; Zhang Y; Cui Q; Wang M; Zhang A; Xia H; Cai T (International Journal of Women's Health)
Chaojin Da,1,2 Junfang Shi,3 Peifen Ma,3,4 Chen Wu,1 Yuxin Zhang,2 Qiongfang Cui,3 Miao Wang,5 Aili Zhang,2 Haozhi Xia,6 Tingting Cai6 1School of Nursing and Rehabilitation, Shandong University, Jinan City, Shandong Province, People’s Republic of China; 2Department of Nursing, School of Clinical Nursing, Gansu Health Vocational College, Lanzhou City, Gansu Province, People’s Republic of China; 3School of Nursing, Lanzhou University, Lanzhou City, Gansu Province, People’s Republic of China; 4Nursing Department, Lanzhou University Second Hospital, Lanzhou City, Gansu Province, People’s Republic of China; 5School of Nursing, WanNan Medical College, Wuhu City, Anhui Province, People’s Republic of China; 6School of Nursing, Fudan University, Shanghai City, People’s Republic of ChinaCorrespondence: Tingting Cai, School of Nursing, Fudan University, No. 305 Fenglin Road, Shanghai, 200032, People’s Republic of China, Tel +86 19821832038, Email caitingtingguo@163.comPurpose: The psychological consequences of pregnancy termination due to fetal abnormalities demonstrate stage-specific characteristics among affected women. With the development of the Internet, social media has increasingly become a significant channel for documenting and sharing health-related experiences. Utilizing journey mapping, this study systematically analyzes self-documented online diaries to explore the experiences of women undergoing induced abortions due to fetal abnormalities across different phases.Patients and Methods: We manually searched three mainstream Chinese text-based social media platforms—Douban, Zhihu, and Jianshu—to collect abortion diaries from user homepages. An interpretative phenomenological thematic content analysis was used to develop journey maps.Results: A total of 278 diaries from 35 users were analyzed, focusing on the experiences of women undergoing pregnancy termination due to fetal abnormalities, which were divided into four phases: diagnostic, inpatient abortion, puerperium, and post-puerperium. Three main themes emerged in each phase: psychological experiences, coping strategies, and post-traumatic transformation. Ten subthemes were identified: grief, emotional responses, self-blame and guilt, cognitive adjustment, seeking social support, recovery, growth, avoidance behaviors, emotional regulation, and shifting attention. Avoidance behaviors occurred in all phases except the puerperium, emotional regulation was present only during inpatient abortion, and shifting attention appeared solely in the puerperium. The remaining subthemes were present across all phases, with varying frequency.Conclusion: Women’s psychological experiences, coping strategies, and post-traumatic transformations vary across stages, highlighting the need for personalized and adaptive nursing care.Keywords: experiences, women’s health, induced abortion, fetal abnormalities, journey map, social media